گوتارە تەفسیریەكانى شێخ محەمەدی خاڵ لە گۆڤاری (گەلاوێژ) دا (لێكۆڵینەوەو هەڵسەنگاندن) - صالح, ئاراس محمد (Sulaimani Journal for Humanities, 2018)
At the end of this paper, the author proposed that at the mid of twentieth century was the most developed period of Kurdish in south of Kurdistan in cultural, social and political issues. At the same time big obstacles occurred awards cultural and social renaissance like political and safety tensions and the Second World War, distribution of illiteracy, economical collapse, and the absent of advanced printing press in Kurdistan. Due to printing of Galawezh journal, the cultural and press movement (1939-1949), at the same time it has a great role in the services of Kurdish language for publishing different articles in history, religion, scientific, literary and Kurdish poem. the study also contain Shekh Muhammad Alkhal life history 1904-1989 as he belongs to the reformist Islamic school with his great efforts in the renewal of Islamic state in Kurdistan by reformist of religious and social states by pressed articles and translation of Quran. Shekh Muhammad Alkhal in his curriculum choose each of Shekh Muhammad Abda and Shekh Muhammad Redha in his translations and he combine between some Qurans ayah and Kurdish circumstances in religious, political and social issues and found the solves of all the problem by Qurans ayah .